Luiz Braga e Milton Hatoum: a “dignificação do anônimo” na fotografia e na literatura - Melo, Adrian Kelly Cardoso (2018)
The main objective of this article is the convergence of the narratives of the works of the photographer from Pará Luiz Braga and the author of the Amazonian Milton Hatoum, discussing the work of these cultural producers: they portray the Amazon in its particularities and unique peculiarities, producing narratives free of stereotypes. The article also discusses the trajectory of both, demonstrating the episode in which the Amazonian writer met the photographer from Pará. Hence the beginning of a dialogic relationship. It is concluded that there is a purpose in Luiz Braga's photography that converges with Milton Hatoum's literary art: the “dignification of the anonymous”. Both, through their arts, bring to light subaltern memories, subsumed histories.